Domestic dogs (Canis familiaris) grieve over the loss of a conspecific - Stefania Uccheddu; Lucia Ronconi; Mariangela Albertini; Stanley Coren; Gonçalo Da Graça Pereira; Loriana De Cataldo; Anouck Haverbeke; Daniel Simon Mills; Ludovica Pierantoni; Stefanie Riemer; Ines Testoni; Federica Pirrone (Scientific Reports, 2022)
Abstract Behavioural reactions towards a dead conspecific have been observed rarely in wild canids and there is no documented scientific evidence of grief in pet dogs. A quantitative analysis of grief-related responses in both dogs and owners was conducted, using the validated online Mourning Dog Questionnaire. The survey was completed by 426 Italian adults who had owned at least two dogs, one of whom died while the other was still alive. This research aims to explore whether, how and what a dog may experience over the loss of a companion dog. Multiple logistic regression indicates that both a friendly or parental relationship between two dogs but also the fact that dogs used to share food and the owner’s grief and anger are principal predictors of negative behavioural changes. According to dog owners’ answers, the surviving dog after the death of the companion dog changed both in terms of activities (“playing”, “sleeping”, and “eating”) and emotions (fearfulness), which occurred as a function of the quality of the relationship between the two animals. By contrast, the time the two dogs had spent together had no effect on the behaviours of surviving dog. Owner perceptions about their dog’s reactions and emotions were not related to the memory or suffering of the event that tended to diminish over time. These findings indicate that a dog may show grief-related behavioural and emotional patterns when a close conspecific dies, with aspects of the latter possibly related to the owner’s emotional status.